Sex on the net: online relations between the men who pay for sex - Earle, Sarah (2008)
[About the Book] How do people have relationships when they are apart, or develop them when they've never even met? From MySpace and weblogs to romance and sexuality, this book draws together a range of studies on remote relationships, investigating the intricate, intimate ways that people forge connections online. The term 'remote' refers to the technologies that facilitate forms of communication, and also underlines the lack of physicality involved in these relationships, developed at a distance. Using empirical data, these collected essays explore a wide variety of relationships, examining the methodological and ethical issues that researchers face. Remote Relationships in a Small World, part of a new generation of online studies, responds to the need for research that focuses on social relationships